FAKTOR PENENTU KESEJAHTERAAN ROHANIWAN HINDU DI BALI (STUDI KASUS IDA PANDITA MPU) - Ayuningsasi, Anak Agung Ketut; Sukadana, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.01.TAHUN.2025, 2025)
Analysis of the well-being of clergy has not been widely conducted. The existence of Hindu clergy, especially Sulinggih, is important in religious activities in Bali. The fact that Sulinggih in Bali are married clergy (Wiku Grhasta), but with limited economic space for movement, directs this study to analyze the determinants of their well-being. The subjects in this study were Sulinggih who came from the Pasek clan (Ida Pandita Mpu). This study used a quantitative approach and was conducted using a survey method by distributing questionnaires to 161 respondents. The sampling technique in this study used saturation sampling. This study uses descriptive analysis, exploratory factor analysis, and regression analysis. Based on the factor analysis, it was concluded that there are three factors that determine the well-being of Ida Pandita Mpu in Bali, namely non-physical functionings, physical functionings, and economic functionings. The well-being of Ida Pandita Mpu in Bali is significantly determined by only the non-physical functionings out of the three. This study supports the notion of functioning, which is a measure for attaining individual well-being, which is one of the ideas of Amartya Sen's theory.